Supportive therapies for prevention of hepatocellular carcinoma recurrence and preservation of liver function - Takami, Taro (World J Gastroenterol, 2016)
Hepatocellular carcinoma (HCC) is one of the deadliest cancers in the world and is associated with a high risk of recurrence. The development of a wide range of new therapies is therefore essential. In this study, from the perspective of supportive therapy for the prevention of HCC recurrence and preservation of liver function in HCC patients, we surveyed a variety of different therapeutic agents. We show that branched chain amino acids (BCAA) supplementation and late evening snack with BCAA, strategies that address issues of protein-energy malnutrition, are important for liver cirrhotic patients with HCC. For chemoprevention of HCC recurrence, we show that viral control after radical treatment is important. We also reviewed the therapeutic potential of antiviral drugs, sorafenib, peretinoin, iron chelators. Sorafenib is a kinase inhibitor and a standard therapy in the treatment of advanced HCC. Peretinoin is a vitamin A-like molecule that targets the retinoid nuclear receptor to induce apoptosis and inhibit tumor growth in HCC cells. Iron chelators, such as deferoxamine and deferasirox, act to prevent cancer cell growth. These chelators may have potential as combination therapies in conjunction with peretinoin. Finally, we review the potential inhibitory effect of bone marrow cells on hepatocarcinogenesis.